Strengthening Student Soft Skills Through Increasing Digital Literacy of Facilities and Infrastructure From an Islamic Education Perspective - Faizin*, Moh.; Hasan, M. Ali; Qolby, Zahra Fatihatul; Nur M, Anisya Putri (Riwayat: Educational Journal of History and Humanities, 2023)
The digital age became a time of many technological and scientific advancements, especially in the world of education. Technological innovation in education has given a new face to the growing and growing learning of today's world. From the medium of conventional learning to the present, it was combined with various technological means. The rapid influx of technological innovations, whether technology in general or technology in the field of makes the impact it produces so significant. Yet while technology and Internet networks are so powerful, it leaves room for the evil that moves within. Because of the lack of digital literacy as a snack for the use of existing technology and the misunderstanding of Muslim education in digital media use as a learning medium and tend to be misunderstood, there is abuse.